Profitabilitas, Ukuran Perusahaan, Reputasi Kantor Akuntan Publik dan Audit Report Lag - Wirayudha, I Putu Bagus Sastra; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 32 No 9 (2022), 2022)
The relevance of financial statements will be lost if there is a delay, such as due to audit report lag. This study aims to determine the effect of profitability, firm size and KAP reputation on audit report lag. The location of the research was carried out on the Indonesia Stock Exchange (IDX) in manufacturing companies for the 2018-2020 period. The sampling technique is purposive sampling with a sample of 135 companies observed. Data were analyzed using multiple linear regression. Based on the analysis, it can be seen that profitability has a negative effect on audit report lag, company size has a negative effect on audit report lag and KAP's reputation has a negative effect on audit report lag. Keywords: Audit Report Lag; Profitability; Company Size; KAP Reputation